HUBUNGAN KADAR HEMOGLOBIN DAN FERITIN DENGAN GAMBARAN KONDUKSI SARAF PADA ANAK TALASEMIA BETA MAYOR - Dewi, Windy Krisanti Kusuma; Gamayani, Uni; Lailiyya, Nushrotul; Reniarti, Lelani; Sekarwana, Nanan (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2018)
CORRELATION BETWEEN HAEMOGLOBINE AND FERRITIN LEVEL WITH NERVE CONDUCTION STUDY IN CHILDREN WITH BETA THALASSEMIA MAJORABSTRACTIntroduction: Beta thalassemia major is inherited hemoglobin synthesis disorder found in thalassemia belt, including Indonesia. Peripheral neuropathy is one of its underdiagnosed neurological complications results in poor management of the patients.Aims: To identify correlation between hemoglobin and ferritin serum with Nerve conduction study (NCS) in Beta thalassemia major patients.Methods: This was a cross-sectional study involving children with beta thalassemia major aged 8-14 years, who regularly underwent blood transfusions in Hasan Sadikin Hospital, Bandung. Nerve conduction study of motor and sensory nerves of all limbs were conducted to the patients. Data was analyzed using Spearman’s correlation analysis.Results: Fifty subjects were included in this study with the mean hemoglobin level (SD) of 6.99 (0.87)g/dL and the mean blood ferritin level (SD) of 3.925 (1.993)μg/L. Based on NCS, most of the subjects had polyneuropathy and 46.94% had axonal demyelinating lesions in sensory and motor nerves. Among patients with neuropathy, there was a statistically significant negative correlation between mean hemoglobin level and the numbers of the abnormal nerves and also a statistically significant positive correlation between mean blood ferritin level and the numbers of the abnormal nerves.Discussion: The lower ferritin serum level, the less nerve involved based on NCS.Keyword: Beta thalassemia, ferritin, hemoglobin, nerve conduction study, neuropathyABSTRAKPendahuluan: Talasemia beta mayor merupakan suatu kelainan sintesis hemoglobin yang herediter yang banyak ditemukan di wilayah tropis, termasuk Indonesia. Salah satu komplikasinya adalah neuropati perifer yang sering tidak terdiagnosis, sehingga penyandangnya tidak mendapatkan tata laksana yang adekuat.Tujuan: Mengetahui hubungan antara kadar hemoglobin dan feritin serum dengan gambaran konduksi saraf (nerve conduction study/NCS) pada penyandang talasemia beta mayor.Metode: Studi potong lintang terhadap penyandang talasemia berusia 8-14 tahun yang rutin menjalani transfusi darah di RSUP Dr. Hasan Sadikin, Bandung. Dilakukan pemeriksaan NCS motorik dan sensorik pada keempat ekstremitas. Data dianalisis menggunakan uji korelasi Spearman.Hasil: Diperoleh 50 subjek dengan rerata kadar hemoglobin 6,99+0,87g/dL dan kadar feritin serum 3.925+1.993μg/L. Berdasarkan pemeriksaan NCS, sebagian besar subjek mengalami polineuropati yang 46,94% di antaranya berupa gambaran demielinasi aksonal sensorik motorik. Pada subjek dengan neuropati perifer didapatkan korelasi negatif yang bermakna antara kadar hemoglobin dengan jumlah keterlibatan saraf pada NCS dan korelasi positif yang bermakna antara kadar feritin serum dengan jumlah keterlibatan saraf pada NCS.Diskusi: Semakin rendah kadar feritin serum, maka semakin sedikit jumlah saraf yang terlibat pada NCS, dan sebaliknya.Kata kunci: Feritin, hemoglobin, nerve conduction study, neuropati, talasemia beta mayor